Factors Associated with Personal Hygiene, use of Personal Protective Equipment, and the Risk of Contact Dermatitis among Scavengers: A Path Analysis Evidence from Surakarta, Central Java - Niken Kartika Sari; Setyo Sri Rahardjo; Vitri Widyaningsih (Journal of Health Promotion and Behavior, 2019)
Background: Scavengers with poor personal hygiene and do not use complete personal protective equipment (PPE) are at risk of developing contact dermatitis. This study aimed to analyze factors associated with personal hygiene, use of personal protectif equipment, and the risk of contact dermatitis among scavengers using path analysis and health belief model.Subjects and Method: This was an analytic observational study with a cross sectional design. The study was conducted at Putri Cempo landfill, Surakarta, Central Java. A sample of 203 scavengers was selected by total sampling. The dependent variable was contact dermatitis. The independent variables were personal hygiene, PPE, perceived susceptibility, perceived severity, perceived benefit, self-efficacy, cues to action, social support, education, and age. The data were collected by questionnaire and analyzed by path analysis.Results: The risk of contact dermatitis was directly and positively affected by poor individual hygiene (b= 4.58; 95% CI= 1.42 to 3.55; p<0.001) and incomplete PPE (b= 5.52; 95% CI= 2.38 to 5.01; p<0.001). The risk of contact dermatitis was indirectly affected by and ages 15-35 years, perceived benefit, cues to action, self-efficacy, perceived susceptibility, perceived severity, low education, and social support.Conclusion: The risk of contact dermatitis is directly and positively affected by poor individual hygiene and incomplete PPE. The risk of contact dermatitis is indirectly affected by and ages 15-35 years, perceived benefit, cues to action, self-efficacy, perceived susceptibility, perceived severity, low education, and social support. Keywords: personal protective equipment, contact dermatitis, personal hygiene, health belief model, path analysis Correspondence:Niken Kartika Sari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: knikenkartika@gmail.com. Mobile: 085229509061.Journal of Health Promotion and Behavior (2019), 4(3): 198-211https://doi.org/10.26911/thejhpb.2019.04.03.05